SUPERVISI AKADEMIK SEBAGAI SALAH SATU UPAYA MENINGKATKAN MUTU PENDIDIKAN - Martinus M. Krowin (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2015)
The improvement of the education quality is the most imporant thing to fulfil the idea of Indonesia.To get this condition ist is related to the role of the teachers for they are he keys to make the program successful of  every effort  to enccourage the quality concernd.It is, therefore, the professsionalism of the teachers concerned must be increased continuously adn one of them is the academic supervision.               A headmaster of a school has to be able to apply the exact nd right sup ervision techniques in realizing the education.  The tecniques of supervision cover the individual and academic ones.               In order to givion of ehe situat the  service and aids in developing the situation or nature of learning and teaching well the supervisors can, therefore, apply the right and it is illustration  of the behaviour pattern  practised   in the supervision approach.